2010
DOI: 10.1111/j.1365-3040.2010.02187.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of ureide accumulation under drought stress in Phaseolus vulgaris L.

Abstract: Under water deficit, ureidic legumes accumulate ureides in plant tissues, and this accumulation has been correlated with the inhibition of nitrogen fixation. In this work we used a molecular approach to characterize ureide accumulation under drought stress in Phaseolus vulgaris. Accumulation of ureides, mainly allantoate, was found in roots, shoots and leaves, but only a limited transient increase was observed in nodules from drought-stressed plants. We show that ureide accumulation is regulated at the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 52 publications
8
67
0
Order By: Relevance
“…The relative independence of ureide-degrading activities and transcript amounts for ALN and AAH from environmental conditions, in particular the status of nitrogen fixation, had been noted earlier (Charlson et al, 2009;Alamillo et al, 2010;Díaz-Leal et al, 2012). ALN activity was independent of tissue ureide influx and ureide content, while AAH activity was only about 50% lower in soybean plants not relying on fixed nitrogen (Winkler et al, 1988;Rice et al, 1990).…”
Section: Discussionmentioning
confidence: 65%
“…The relative independence of ureide-degrading activities and transcript amounts for ALN and AAH from environmental conditions, in particular the status of nitrogen fixation, had been noted earlier (Charlson et al, 2009;Alamillo et al, 2010;Díaz-Leal et al, 2012). ALN activity was independent of tissue ureide influx and ureide content, while AAH activity was only about 50% lower in soybean plants not relying on fixed nitrogen (Winkler et al, 1988;Rice et al, 1990).…”
Section: Discussionmentioning
confidence: 65%
“…Genes involved in ureide synthesis and degradation have been shown to be induced upon stress conditions. Higher ureide concentrations, mainly in form of allantoate, were previously reported in shoots and leaves of common bean (Phaseolus vulgaris) during drought treatment and this was not a consequence of suppression of allantoate degradation, but rather, an induction of biosynthesis regulated at the transcript level (Alamillo et al 2010, Coleto et al 2014). While we were unable to determine specifically which ureide was contributing to this increase, as only bulk measurements were performed, it also appears that in Eutrema growth irradiance may influence ureide accumulation at the level of transcription.…”
Section: Resultsmentioning
confidence: 54%
“…However the ureide levels have been shown to rise under water stress conditions also, and it has been suggested that the accumulation of ureides responsible for the feedback inhibition of nitrogen fixation in adverse conditions [32,33]. Recently reported that ureide content increases considerably in nonnodulated common bean plants suffering water stress and drought-induced senescence was considered the possible source of ureides [5]. An increase in uriede content of soybean leaves has been reported by Yukimoto and Ishianj after application of some oroganophosphorus insecticides [34].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the correlation between nitrogen fixation and ureide levels with transition to reproductive development have been clearly demonstrated [4]. The major accumulation of ureides occurs has completely inhibited the N 2 fixation in nodulated plants [5]. Remobilization of nitrogen from senescent tissues was suggested as the most likely alternative source of ureides and involved in the N-feedback regulation of nitrogen fixation [6].…”
Section: Introductionmentioning
confidence: 99%